DEVELOPMENT AND RESEARCH OF A MATHEMATICAL MODEL OF A SOLAR PHOTO CONVERTER WITH AN INVERTER FOR CONVERTING DIRECT CURRENT TO ALTERNATING VOLTAGE - M. Kalimoldayev; M. Akhmetzhanov; M. Kunelbayev (Academic Scientific Journal of Computer Science, 2019)
This article presents a mathematical model of photovoltaic systems. For the analysis of energy processes in autonomous power transmission systems, it is now advisable to use computer simulation methods. The use of a simulation model makes it possible to provide an energy balance in an autonomous power transmission system with specific energy characteristics of ground and buffer sources of energy and a time scale from the power consumption of the load. This allows you to influence the energy characteristics of transmission systems to ensure the energy balance in the system in terms of temporary changes in the energy characteristics of energy sources, as well as the impact on the energy characteristics of the systems of transmission parameters such as solar energy. lighting, temperature, time of year, etc. This model is described by the current-voltage characteristic (CVC) at a given temperature, and the lighting conditions are the basis for calculating the parameters of the photoelectric energy in a wok. A new inverter was also designed and researched to convert direct current into alternating voltage, which allowed saving from 18.5% to 35.19% of expensive solar photo converters.